Why deer? Figural imagery and faunal remains in the Bronze Age South Caucasus* - Rubinson, Karen S. (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
Deer were part of the domestic debris in the South Caucasus at least since the Early Bronze Age and were represented on Kura-Araxes ceramics in stylized form. In the Middle Bronze Age, deer remains appeared in burial contexts, both as faunal remains and visual representations. In the Late Bronze Age, deer hunted from chariots and also as single figures decorated devices that were attached to the yokes of the animals that pulled wheeled vehicles. It is suggested that deer may be an expression of spiritual practice, carrying a different meaning than the other scenes and animals that also populate these yoke devices.